THE ANALYSIS AND THE DESIGN OF E-MARKETING STRATEGY AT SME’S (A CASE STUDY: THE DARE TO DREAM INDONESIA COMMUNITY) - Ongowarsito, Henkie; Nurcahyani, Kartika; Djoyo, Brata Wibawa (Bina Nusantara University, 2011)
The purposes of the research are to analyze the e-marketing strategy and to design e-marketing application which is a website that is appropriate for SME’S of Dare to Dream Indonesia (D2DI) community. The methodology of analysis used consists of 4 stages from 7 stages of e-marketing and the design method consists of three last stages of e-marketing. The result achieved is a website as an e-marketing application that can support marketing and promoting activities, expanding the target market, giving complete information and facilitating the customers to access product information, and supporting the communication between D2DI community, SME’S, and the customers. The conclusions obtained are that e-marketing can be a solution to solve customer needs of the availability of complete and current information and communication.Keywords: Information System, content management system, academic development